Express your feelings in words when you get sick of others’ pain: Effects of word labeling on pain empathy in phase-amplitude coupling - Jiahe Sun; Wenguang He; Hongfei Ji; Jie Li; Jie Zhuang (NeuroImage)
Revealing the neurophysiological mechanisms underlying pain empathy has profound implications for the understanding of social emotions and pain regulation. This study aimed to elucidate the mechanisms by which pain empathy modulates individual experiences, focusing on two primary questions: When individuals empathize with pain, do they attend more to the emotional content associated with pain or the nociceptive experience itself? How does lexical labeling modulate negative affect during pain empathy? In this EEG study, we employed a labeling paradigm divided into pain labeling, affect labeling and tool labeling to distinguish emotional content from the nociceptive experience of pain stimuli. We collected data from 39 participants and analyzed their EEG components and frequency-specific brain activity across the experimental conditions. Cross-frequency coupling analyses were conducted to uncover the mechanisms by which pain empathy modulates emotional responses. Our findings revealed that compared to pain labeling and tool labeling, affect labeling more effectively reduces the negative affect associated with pain empathy. This was evidenced by the decreased amplitude of the P300 component and lower theta-band activity within the prefrontal cortex, predominantly during the later stages of labeling. Additionally, affect labeling was associated with enhanced theta-gamma phase-amplitude coupling, with theta phase modulation in the posterior parietal and sensorimotor cortices influencing prefrontal gamma-band activity. These results suggest that, during pain empathy, individuals allocate greater attentional and cognitive resources to the emotional aspects of pain. Thus, implicit regulation of pain empathy involves coordinated interactions across multiple brain regions.